2002
DOI: 10.1046/j.1440-169x.2002.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting planarian central nervous system regeneration by the expression of neural‐specific genes

Abstract: The planarian central nervous system (CNS) can be used as a model for studying neural regeneration in higher organisms. Despite its simple structure, recent studies have shown that the planarian CNS can be divided into several molecular and functional domains defined by the expression of different neural genes. Remarkably, a whole animal, including the molecularly complex CNS, can regenerate from a small piece of the planarian body. In this study, a collection of neural markers has been used to characterize at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 41 publications
2
136
0
Order By: Relevance
“…Also, transient structures like the blastema are not always useful for comparative studies across distant taxa. Where blastemas can be characterized by a mass of cells clustering in the area of the wound after closure, leading to growth and regeneration into new organs or new body parts, it has been shown that the histological nature of this mass of cells is different in different regenerative structures (Shibata et al, 1999;Cebrià et al, 2002;Bosch et al, 2008;Kragl et al, 2009;Wenemoser and Reddien, 2010;Aboobaker, 2011;Reddien, 2013;Bely et al, 2014). Additionally in some epimorphic regenerative events, i.e., where local stimulation of cell proliferation precedes the development of the new part, there is a lack of structures that resemble a blastema, such as during the Ciona intestinalis siphon regeneration (Auger et al, 2010) or the whole body regeneration in colonial ascidians (Brown et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…Also, transient structures like the blastema are not always useful for comparative studies across distant taxa. Where blastemas can be characterized by a mass of cells clustering in the area of the wound after closure, leading to growth and regeneration into new organs or new body parts, it has been shown that the histological nature of this mass of cells is different in different regenerative structures (Shibata et al, 1999;Cebrià et al, 2002;Bosch et al, 2008;Kragl et al, 2009;Wenemoser and Reddien, 2010;Aboobaker, 2011;Reddien, 2013;Bely et al, 2014). Additionally in some epimorphic regenerative events, i.e., where local stimulation of cell proliferation precedes the development of the new part, there is a lack of structures that resemble a blastema, such as during the Ciona intestinalis siphon regeneration (Auger et al, 2010) or the whole body regeneration in colonial ascidians (Brown et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated precisely how the neurons in each domain are connected by analysing the projection patterns of each domain in detail by DiI/DiD tracing (Okamoto et al 2005). Also, we found that a planarian netrin homologue (Djnetrin) is expressed in the junctions between visual neurons and the brain as well as between the VNCs and the brain (Cebrià et al 2002c;Cebrià & Newmark 2005). These analyses suggested that a variety of external signals received by these sensory neurons may be integrated in the DjotxBexpressing domain, where dopaminergic neurons are concentrated (Nishimura et al 2007), and that these integrated signals may be transferred to the body muscles through the VNCs (Tazaki et al 1999).…”
Section: Structure Of the Planarian Brainmentioning
confidence: 99%
“…Interestingly, most of these genes are expressed in distinct domains of the intact brain and at distinct stages during the brain regeneration. They can be classified into four classes according to their expression timing during the process of brain regeneration: early; early-middle; late-middle; and late genes (Cebrià et al 2002c ). These results suggested that clathrin-mediated endocytic signals may be required not only for the maintenance of neurons after synaptic formation, but also for axonal extension at the early stage of brain regeneration.…”
Section: Screening Of Genes Involved In the Brain Regenerationmentioning
confidence: 99%
“…Large-scale expression analyses have revealed that many neural genes involved in vertebrate brain development and function are also expressed in distinct domains of the planarian CNS [13,14]. These results indicate that the planarian CNS is functionally regionalized according to a discrete expression of neural-specific genes.…”
Section: Da Neuronal Regeneration In Regenerative Animalsmentioning
confidence: 98%